2016
DOI: 10.1167/iovs.15-17328
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Ganglion Cell and Inner Plexiform Layer Loss Correlate with Visual Acuity Loss in LHON: A Longitudinal, Segmentation OCT Analysis

Abstract: For the first time these analyses describe a structure-function relationship between the retinal changes that occur in LHON patients as their disease progresses and vision worsens. The structural changes in the GCL, IPL, and RNFL preceded structural changes in the other retinal layers. This analysis suggests that the first 6 months after diagnosis define a target for therapeutic intervention, and this can inform treatment guidelines for ongoing therapeutic trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…Central field defects and blind spot enlargement were common findings, in keeping with previous investigations [18]. e current study showed that that the thickness of the RNFL around the optic disc and surrounding the macula did not reduce in the acute stage but reduced significantly in the chronic stage of the disease, corroborating previous reports [19,20]. e pattern ERG N95 and approximately 70% of P50 originate in the retinal ganglion cells.…”
Section: Discussionsupporting
confidence: 92%
“…Central field defects and blind spot enlargement were common findings, in keeping with previous investigations [18]. e current study showed that that the thickness of the RNFL around the optic disc and surrounding the macula did not reduce in the acute stage but reduced significantly in the chronic stage of the disease, corroborating previous reports [19,20]. e pattern ERG N95 and approximately 70% of P50 originate in the retinal ganglion cells.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies previously reported a relationship between visual acuity and GCIPL thickness that was related to the pathophysiology of each optic neuropathy. Kim et al 16 demonstrated that thinning of the superior and inferior GCIPL was significantly correlated with visual acuity in severe glaucoma, and Moster et al 17 reported that a decrease in GCIPL thickness was associated with worsening vision in the acute phase of LHON. 17 In addition to those optic neuropathies, we found a significant effect of GCIPL thickness on the potential for visual recovery in patients with EON.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 16 demonstrated that thinning of the superior and inferior GCIPL was significantly correlated with visual acuity in severe glaucoma, and Moster et al 17 reported that a decrease in GCIPL thickness was associated with worsening vision in the acute phase of LHON. 17 In addition to those optic neuropathies, we found a significant effect of GCIPL thickness on the potential for visual recovery in patients with EON. In our results, as the thickness of the remaining GCIPL increased and the damage to the GCIPL decreased during 6 months of follow-up, the possibility of visual acuity recovery before permanent retinal ganglion cell death increased.…”
Section: Discussionmentioning
confidence: 99%
“…Other OoC devices with higher degrees of complexity and multi-compartmental organization, such as brain tissues (e.g., blood-brain-barrier (BBB) chips) and the human eye (eye-on-a-chip) [ 88 , 89 ], exhibit design challenges beyond what is shown here for the HoC. For example, to recapitulate the membrane structure of blood capillaries in the brain or to recapitulate the functions of the multi-layer cellular assemblies of the cornea [ 29 ] and retina [ 90 ] or the blinking function of the eyelid [ 91 ] requires elaborate design efforts. Especially, the integration with the surrounding biopolymers (ECMs and membranes) forming scaffolds for realizing the 3D architecture of the organ then becomes an essential function in the design.…”
Section: Discussionmentioning
confidence: 99%